2020
DOI: 10.3390/jcm10010028
|View full text |Cite
|
Sign up to set email alerts
|

Convalescent Plasma Transfusion for the Treatment of COVID-19—Experience from Poland: A Multicenter Study

Abstract: Because the optimal treatment for COVID-19 is still unknown, it is important to explore every potential way of improving the chances of survival for COVID-19 patients. The aim of the study was to analyze the effectiveness of convalescent plasma on COVID-19 patients. The study population consisted of 78 patients diagnosed with COVID-19, selected from the SARSTer national database, who received convalescent plasma. The impact on clinical and laboratory parameters was assessed. A clinical improvement was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 14 publications
1
36
0
1
Order By: Relevance
“…A total of 4728 records were identified from databases, websites and citation searching. There were 47 studies 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 fulfilled the inclusion criteria and were used for the systematic review and meta‐analysis (Figure 1 ). Of 47 included studies, 21 were clinical trials 16 , 17 , 18 ,…”
Section: Resultsmentioning
confidence: 99%
“…A total of 4728 records were identified from databases, websites and citation searching. There were 47 studies 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 fulfilled the inclusion criteria and were used for the systematic review and meta‐analysis (Figure 1 ). Of 47 included studies, 21 were clinical trials 16 , 17 , 18 ,…”
Section: Resultsmentioning
confidence: 99%
“…A matched propensity score study published by Salazar and colleagues found the greatest effect when patients were given CP within 44 h of hospital admission [24]. Thus, thanks to these and other similar studies [25], nowadays we are aware that CP must be administered early, possibly within 72 h from symptom onset [26]. Other RCTs [27,28] did not find clinical benefit from later CP administration.…”
Section: The Diseasementioning
confidence: 92%
“…This scale is based on WHO recommendations modified to fit the specificity of the national health care system as applied previously. 11 , 12 Clinical improvement was defined as at least a 2-point decrease from baseline to 14, 21, and 28 days of hospitalization. The ordinal scale was scored as follows: 1) unhospitalized, no activity restrictions; 2) unhospitalized, no activity restrictions and/or requiring oxygen supplementation at home; 3) hospitalized, does not require oxygen supplementation and does not require medical care; 4) hospitalized, requiring no oxygen supplementation, but requiring medical care; 5) hospitalized, requiring normal oxygen supplementation; 6) hospitalized, on non-invasive ventilation with high-flow oxygen equipment; 7) hospitalized, for invasive mechanical ventilation or extracorporeal membrane oxygenation (ECMO); and 8) death.…”
Section: Methodsmentioning
confidence: 99%